Clinical pain management : a practical guide - 4 0 16; 1937- Lynch, Mary E.,;Craig, Kenneth D.,;Peng, Philip W. H.; 5 (Hoboken, NJ : Wiley-Blackwell, 2022)
In his Foreword to the first edition of this book, Clinical Pain Management: A Practical Guide, Ron Melzack emphasised that pain has many dimensions and that despite advances in pain management and understanding, chronic pain in particular continues to be a major health concern. This unfortunately is still the case, and many challenging problems still exist in managing and understanding chronic pain. The Introductory chapter of this second edition of the book by its three editors, Drs. Lynch, Craig and Peng, draws attention to the challenges that exist for people living with chronic pain conditions, for the clinician trying to provide effective management of the patient's pain, for the scientist seeking to unravel the mechanisms underlying pain, and for society as a whole. These challenges stem from the complexity and multidimensional nature of chronic pain, the limited understanding of the processes underlying most chronic pain conditions, and the variety of diagnostic and therapeutic approaches advocated for pain management, some of which have little or no solid scientific evidence base to support their use--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; therapy;methods -- Pain Management;Chronic Pain;Palliative Care -- 20; 20; 2